Integrating local culture into IPAS learning: A culturally responsive teaching approach in elementary school - Avhiony Puspa Sari; Maharani Putri Kumalasani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Education in the era of globalization faces various challenges, including accommodating cultural diversity, particularly students' diverse cultural backgrounds. This study explores the implementation and integration of local culture through a Culturally Responsive Teaching approach in science and social studies (IPAS) lessons for fourth-grade students at SDN Junrejo 1, Batu. Through Hernandez's theoretical perspective, which covers five aspects, namely: content integration (combining material with cultural context), facilitating knowledge construction (constructing knowledge according to cultural background), reducing prejudice (reducing bias on differences), social Justice (becoming agents of change), and academic development (helping students achieve academic success). This study used a descriptive qualitative research method. The subjects in this study included teachers and fourth-grade students at SDN Junrejo 1, Batu. The results of this study indicate that the school's efforts to develop culture-based activities and the fourth-grade teachers' efforts to integrate local culture into IPAS learning have made learning relevant and meaningful. The conclusion of this study shows that integrating local culture into IPAS learning can help students understand scientific and social concepts in context. With the school's support, students are motivated to recognize, appreciate, and preserve their culture. This study provides a new contribution to implementing Culturally Responsive Teaching (CRT) practices based on Hernandez's five aspects in the context of science and mathematics learning, a topic rarely discussed comprehensively.